Industry and Tertiary Sectors towards Clean Energy Transition - Toro, Claudia; Martini, Chiara (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The clean energy transition is the transition from the use of nonrenewable energy sources to renewable sources and is part of the wider transition to sustainable economies through the use of renewable energy, the adoption of energy-saving measures, and sustainable development techniques. The clean energy transition is a long and complex process that will lead to an epochal change, and it will allow safeguarding the health of the environment in the long term. For its success, it necessitates contribution from everyone, from the individual citizen to large multinationals, passing through SMEs; national and international policies play a key role in paving the way to this process. This Special Issue is focused on technical, financial, and policy-related aspects linked to the transition of industrial and service sectors towards energy saving and decarbonization. These different aspects are interrelated and, as such, they have been analyzed with an interdisciplinary approach, for example, by combining economic and technical information. The collected papers focus on energy efficiency and clean-energy key technologies, renewable sources, energy management and monitoring systems, energy policies and regulations, and economic and financial aspects.